Information and Communication Technologies (ICT) in Medical Education and Practice: The Major Challenges - Karsenti, Thierry; Charlin, Bernard (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2008)
AbstractThis literature review addresses the main effects and challenges in using information and communication technologies (ICT) in medical education and practice. The first challenge is to better prepare future physicians for the changing behaviours of patients, who are increasingly Internet-savvy and who sometimes appear to know more about their diseases than their physicians. The second challenge, which is closely linked to the first, is to raise awareness among physicians in training of the many benefits of using ICT to improve not only the quality of interventions and health care delivery but, from a broader perspective, the organization of the health care system itself. The third challenge is to motivate medical students and practitioners to use ICT to find information, learn and develop. It is proposed that information literacy should be a mandatory skill for all medical students. The e-learning mode of training is also addressed. Although underemployed in most medical faculties, it represents the future of initial and continuous medical training. Virtual resources and communities, simulations and 3D animations are also discussed. The fourth and final challenge is to change medical teaching practices.